EMPLOYEE PERFORMANCE ROLE: JOB STRESS AND JOB SATISFACTION - Muhammad Ras Muis (CERED Indonesia Institute, 2021)
This study aims to determine the effect of skills and motivation on work performance at PT. State Savings Bank The purpose of this study is to identify and analyze the impact of work stress on employee performance, identify and analyze the impact of discipline on employee performance, and to know partially or simultaneously the impact of work stress and discipline on employee performance. human resources department of PT. PLN Medan Customer Service. The approach used in this study is a quantitative and associative approach. The population of this study were all employees of the HR department of PT. The customer service unit of PLN (Persero) Medan amounted to 74 people, but the number of samples that met the sampling criteria for observations made were 74 people using the saturated sampling technique. Data collection methods in this study used interviews and questionnaires. The data analysis technique in this study uses classical hypothesis testing, multiple regression, hypothesis testing (T-test and F-test), and the coefficient of determination. The data processing of this research used the Social Science Statistics Package (SPSS) version 22.00. The results of this study partially indicate that work stress has a positive and significant effect on employee performance, and job satisfaction has a positive and significant effect on the performance of employees who are members of the HR department of PT. PLN (Persero) Medan customer service implementing unit. Meanwhile, job stress and job satisfaction are known to have a significant positive effect on employee performance in the human resources department of PT. PLN Medan customer service implementation unit hypothesis testing (T-test and F-test), and the coefficient of determination. The data processing of this research used the Social Science Statistics Package (SPSS) version 22.00. The results of this study partially indicate that work stress has a positive and significant effect on employee performance, and job satisfaction has a positive and significant effect on the performance of employees who are members of the HR department of PT. PLN (Persero) Medan customer service implementing unit. Meanwhile, job stress and job satisfaction are known to have a significant positive effect on employee performance in the human resources department of PT. PLN Medan customer service implementation unit hypothesis testing (T-test and F-test), and the coefficient of determination. The data processing of this research used the Social Science Statistics Package (SPSS) version 22.00. The results of this study partially indicate that work stress has a positive and significant effect on employee performance, and job satisfaction has a positive and significant effect on the performance of employees who are members of the HR department of PT. PLN (Persero) Medan customer service implementing unit. Meanwhile, job stress and job satisfaction are known to have a significant positive effect on employee performance in the human resources department of PT. PLN Medan customer service implementation unit The results of this study partially indicate that work stress has a positive and significant effect on employee performance, and job satisfaction has a positive and significant effect on the performance of employees who are members of the HR department of PT. PLN (Persero) Medan customer service implementing unit. Meanwhile, job stress and job satisfaction are known to have a significant positive effect on employee performance in the human resources department of PT. PLN Medan customer service implementation unit The results of this study partially indicate that work stress has a positive and significant effect on employee performance, and job satisfaction has a positive and significant effect on the performance of employees who are members of the HR department of PT. PLN (Persero) Medan customer service implementing unit. Meanwhile, job stress and job satisfaction are known to have a significant positive effect on employee performance in the human resources department of PT. PLN Medan customer service implementation unit Job stress and job satisfaction are known to have a significant positive effect on employee performance in the human resources department of PT. PLN Medan customer service implementation unit Job stress and job satisfaction are known to have a significant positive effect on employee performance in the human resources department of PT. PLN Medan customer service implementation unit.